UPAYA PENANGGULANGAN TINDAK PIDANA PERKOSAAN DENGAN SARANA PENAL DALAM RANGKA MELINDUNGI PEREMPUAN - Ramiyanto, Ramiyanto; Waliadin, Waliadin (Jurnal Legislasi Indonesia, 2018)
Rape is one of the criminal acts regulated in the Criminal Code as stated in Article 285. When viewed from the formulation, the crime of rape stipulated in the provision is included in the type of formal crime. Article 285 of the Criminal Code has set limits on the meaning of rape and its elements but is not given an explanation of the meaning of each of these elements. Therefore, the granting of the meaning of each element of criminal acts of rape is seen in the doctrine and practice of criminal justice that has occurred so far. In its development, handling effort to criminal acts of rape by means of penal (criminal law) experienced a shift in the form of expanding the meaning of elements of “violence or threat of violence” as can be seen in the decision number: 410/Pid.B/2014/PNBgl. This element is not only classically interpreted, but also includes the persuasion accompanied by false promises. In the context of the protection of women, the decision should be appreciated and should be used as a reference by the judge in handling the same case even though it was not followed by the High Court and the Supreme Court. The expansion of the meaning of “violence or threat” as an element of criminal acts of rape can also be used as input for reforming criminal law in Indonesia.